443 Impact of ergot alkaloids fed during gestation on fetal growth and subsequent postnatal growth in ewe lambs. (7th December 2018) - Britt, J; Adams, S; Miller, M; Kojima, C; Andrae, J; Duckett, S
Abstract: Consumption of ergot alkaloids during gestation negatively impacts fetal growth and development in utero. The objective of this study was to evaluate these impacts on the growth, and development in ewe lambs post-weaning. Suffolk ewes (n = 60; 83.1kg) estimated to be carrying twins at d 35 of gestation were stratified by genotype (AA, AG, GG; DRD2 SNP) to: endophyte-free tall fescue seed (E-; 0.0 µg ergovaline + ergovalinine/g seed) or endophyte-infected tall fescue seed (E+; 4.14 µg ergovaline + ergovalinine/g seed) during MID gestation (d 35 – 85) or LATE gestation (d 86 – parturition). Endophyte-infected tall fescue seed provided 1772 µg of ergovaline + ergovalinine/hd/d for E+ treatment while endophyte-free seed (0.0 µg ergovaline + ergovalinine) was fed for E- treatment. This created four unique treatments: E-/E-, E-/E+, E+/E-, and E+/E+. Data were analyzed as a randomized block design with maternal genotype (AA, AG, GG), fescue treatment, and interactions as fixed effects. Weights of lambs born to these ewes were collected at birth and weaning. Weights of ewe lambs (n = 39) were collected every two weeks until d 126 post-weaning. Lambs born to ewes on E+/E+ and E-/E+ treatment had lighter ( P < 0.05) birthweights compared to lambs born to E-/E- ewes. Weaning weight for all lambs was lower ( P < 0.05) for E+/E+ lambs. There was an interaction ( P = 0.10) between time and treatment for ewe lamb weight post-weaning wherein ewe lambs born to ewes on E+/E- treatment had higher weights at d 28 and d 42 post-weaning and ewe lambs born to ewes on E-/E+ treatment had the lowest bodyweights throughout the post-weaning period. Yearling weights did not differ ( P > 0.10) by treatment or ewe genotype. Maternal consumption of ergot alkaloids negatively impacts ewe lamb growth during the post-weaning period.